Analysis of the Physical-Mechanical Properties of a Pelleted Chicken Litter Organic Fertiliser - Brunerová, A.; Müller, M.; Gürdil, G.A.K.; Šleger, V.; Brožek, M. (Czech Academy of Agricultural Sciences, 2020)
Pelleted fertiliser production represents improvements in fertiliser management and ensures several benefits, such as a more accurate dosing (less applications), the slow-release of long-lasting nutrients, the possible application during the whole year, easier storage and transportation and better separation of fertilisers and pesticides. The present research investigated the physical-mechanical properties of a pelleted chicken litter organic fertiliser. The pellet samples' particle density ρ (kg·m-3), mechanical durability DU (%), compressive strengths in the cleft σc (N·mm-1) and in simple pressure σp (MPa) were investigated. The last two indicators, σc and σp, demonstrated the pellets' resistance to the compressive stress. The resulting values proved ρ = 1 289.73 kg·m-3, DU = 95.5%, σc = 58.61 N·mm-1 and σp = 20.02 MPa, while all the results were evaluated positively. The observed level of the DU (%) did not achieve the mandatory level for the commercial production of pellets (DU = 97.5%), however, such a level is stated for a pellet solid biofuel intended for energy production. Therefore, the achieved level of the DU (%) represents a satisfactory result within the investigated pellet samples' mechanical quality. In general, the viability and practicability of chicken litter pellet production was proven, as well as, the suitability of such a feedstock for pellet production. Moreover, the observed results proved a high level of the investigated pellet samples' mechanical quality. © 2020 Czech Academy of Agricultural Sciences. All rights reserved.
Keywords: Compression Force; Densification Process; Pellet Strength; Poultry Manure; Sustainable Technology